Association of UGT1A1 Genetic Variants with Increases in Bilirubin Levels (Precision Medicine Communications, 2022)
For patients that are intolerant or resistant to the disease-modifying-antirheumatic-drugs (DMARDS) or suffer from mild to moderate rheumatoid arthritis (RA), a human monoclonal antibody targeting interleukin (IL)-6Rα called Sarilumab is approved for use. Patients who are given Sarilumab are reported to have mild abnormalities in the AST/ALT levels. Lin and colleagues performed a genome-wide investigation into the elevated levels of bilirubin in patients suffering from RA and are being administered Sarilumab. DNA samples of 1075 patients were subjected to exome sequencing and genotyping. Their findings reveal that maximum elevations in bilirubin levels are associated with variants of the UGT1A1 gene (rs4148325; p = 2.88 × 10−41) but ALT/AST elevations harbored no such association. Other independent loci failed to have any associations in Sarilumab prescribed patients having bilirubin elevations. The authors argue that variants of the UGT11 gene are associated with bilirubin increase in RA patients taking Sarilumab. Pharmacogenomics J. 2022 May;22(3):160-165.